One-loop Form Factors for \(H→ γ^*γ^*\) in \(R_ξ\) Gauge - Phan, Khiem Hong; Tran, Dzung Tri (Communications in Physics, 2022)
In this paper, we present general one-loop form factors for \(H→ γ^* γ^*\) in \(R_ξ\) gauge, considering all cases of two on-shell, one on-shell and two off-shell for final photons. The calculations are performed in standard model and in arbitrary beyond the standard models which charged scalar particles may be exchanged in one-loop diagrams. Analytic results for the form factors are shown in general forms which are expressed in terms of the Passarino-Veltman functions. We also confirm the results in previous computations which are available for the case of two on-shell photons. The \(ξ\)-independent of the result is also discussed. We find that numerical results are good stability with varying \(ξ=0,1\) and \(ξ→ ∞\).